Opportunistic insects associated with pig carrions in Malaysia - Heo, Chong Chin; Hiromu Kurahashi,; Mohamed Abdullah Marwi,; John Jeffery,; Baharudin Omar, (Universiti Kebangsaan Malaysia, 2011)
Flies from the family Calliphoridae, Sarcophagidae and Muscidae are usually found on human cadavers or animal carcasses. However, there are many other families of Diptera and Coleoptera that were found associated with animal carcasses, which have not been reported in Malaysia. In this paper, we report dipterans from the family Micropezidae: Mimegralla albimana Doleschall, 1856, Neriidae: Telostylinus lineolatus (Wiedemann 1830); Sepsidae: Allosepsis indica (Wiedemann 1824), Ulidiidae: Physiphora sp. and a beetle (Coleoptera: Hydrophilidae: Sphaeridium sp.) as opportunist species feeding on oozing fluid during the decomposition process. They did not oviposit on the pig carcasses, therefore, their role in estimation of time of death is of little importance. However, they could provide clues such as locality and types of habitats of the crime scene.